GAMBARAN ASUPAN PURIN PADA REMAJA DI KABUPATEN MINAHASA - Ali, Ningsi Hadji; Kepel, Billy J.; Bodhi, Widdhi (eBiomedik, 2013)
Abstract: High purine intake can result in hyperuricemia which leads to gouthy arthritis and formation of kidney stone. High purine concentration is mainly contained in animal protein. Minahasa ethnic people have a habit of holding events where there is feast party and the majority of Minahasa signature dishes are animal product. This study aims to describe the purine intake in adolescents in Minahasa Regency. This research design is a descriptive cross-sectional study with 40 study subjects. Sample is students of SMKN 2 and SMKN 3 Tondano in Minahasa Regency. Purine intake is measured by using Food Frequency Questionnaire (FFQ). The average of purine intake among adolescents in Minahasa Regency is 91,89 to 1028,44 mg/day, 40% adolescents consume purine rich foods, that consist of 35% boys and 5% girls. There are 52,5% adolescents consume foods with moderate purine content in high frequency and 40% adolescents consume foods with high purine content in high frequency. The conclusion of this study is the average of purine intake among adolescents in Minahasa Regency is quite high. It requires dietary knowledge of purine containing foods in order to reduce purine intake to prevent the increasing of hyperuricemia incidence and its impacts. Keywords: purine intake, adolescent, Minahasa Regency Â  Â  Abstrak: Asupan purin yang tinggi dapat menyebabkan terjadinya hiperurisemia yang dapat berakhir dengan gout arthritis dan batu ginjal. Kadar purin yang tinggi terutama terkandung dalam protein hewani. Masyarakat etnis Minahasa memiliki kebiasaan menggelar acara syukuran yang diikuti dengan pesta makan dan makan makanan khas Minahasa yang sebagian besar berasal dari hewani. Penelitian ini bertujuan untuk mengetahui gambaran asupan purin pada remaja di Kabupaten Minahasa. Penelitian ini menggunakan desain deskriptif cross-sectional dengan jumlah subjek 40 orang. Subjek dari penelitian ini yaitu siswa-siswi SMK Negeri 2 Tondano dan SMK Negeri 3 Tondano di Kabupaten Minahasa. Data asupan purin diukur dengan Food Frequency Questionnaire (FFQ). Rata-rata asupan purin remaja di Kabupaten Minahasa sebesar 91,89-1028,44 mg/hari, dengan 40% remaja mengkonsumsi purin dalam jumlah yang tinggi, yang terdiri dari 35% remaja pria dan 5% remaja wanita. Remaja yang mengkonsumsi makanan yang mengandung purin sedang dengan frekuensi tinggi sebanyak 52,5% dan remaja yang mengkonsumsi makanan yang mengandung purin tinggi dengan frekuensi tinggi sebanyak 40%. Kesimpulan penelitian ini yaitu rata-rata asupan purin remaja di Kabupaten Minahasa cukup tinggi. Hal ini membutuhkan peningkatan pengetahuan tentang kandungan purin dalam makanan sehingga dapat membatasi jumlah asupan purin untuk mencegah meningkatnya kejadian hiperurisemia dan penyakit yang ditimbulkannya. Kata kunci: asupan purin, remaja, Kabupaten Minahasa